Foot problem and foot care practice among diabetic patient in a primary care clinic - Jamani, Nurjasmine Aida (2014)
Diabetes mellitus is a global health problem with diabetic foot being one of the complication which can lead to amputation.In 2003, Malaysia’s prevalence of diabetic foot ulcer is 6%.Poor foot care practice is one of the factor for diabetic foot problem.Currently, there is limited data on type of foot problem and foot care practice among Malaysian diabetic patients.